Pengalaman Komunikasi dan Identitas Diri Pelaku Cosplayer Anime Perempuan - Nurjanah,, Nadilawati Kurwiniarti; Abidin, Zainal; Nurkinan, Nurkinan (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
This study uses a qualitative method and a phenomenological approach, because in this study, researchers examine a phenomenon that aims to find out the communication experiences experienced by female cosplayers in Jabodetabek. This study uses observation techniques, in-depth interviews, and analysis of the data needed. Research is going well and researchers must seek in-depth information in order to get what is actually needed. The theory used in conducting this research is the phenomenological theory of Alfred Schutz which is the basis for this research. The results obtained from this study after obtaining data from informants show that the communication experience of female cosplayers in Jabodetabek. Cosplayer is identity and happiness, where a high sense of love for anime characters becomes a motivation to form oneself and not give up. Motives for liking anime characters and becoming a cosplayer are their families who support fans of anime characters. socializing and forming relationships is also one of the reasons for being a Cosplayer, financial readiness before it has to be carried out in a mature manner. Self-identity is independence arising from feelings of worth, ability and self-mastery.The difference in the meaning of social construction or reality depends on experience, education, social or social environment of each individual. Experience is one of the keys to moving forward. Doing Fan Service always greets fans, invites photos together. Keywords: Phenomenology,Cosplayer, Communication Experience, Social Reality.